New species of scaly crickets (Orthoptera: Mogoplistinae) from Bukit Fraser, Malay Peninsula - Tan, Ming Kai; Kamaruddin, Khairul Nizam (Zootaxa, 2013)
Two new species of Mogoplistinae from Bukit Fraser, Pahang of Malay Peninsula are described: Micrornebius malaya sp. n. and Ornebius albalatus sp. n.